2007
DOI: 10.1016/j.taap.2006.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Tea and cancer prevention: Molecular mechanisms and human relevance

Abstract: Tea made from the leaves of the plant Camellia sinensis is a popular beverage. The possible cancer preventive activity of tea and tea polyphenols has been studied extensively. This article briefly reviews studies in animal models, cell lines, and possible relevance of these studies to the prevention of human cancer. The cancer preventive activity of tea constituents have been demonstrated in many animal models including cancer of the skin, lung, oral cavity, esophagus, stomach, liver, pancreas, small intestine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
169
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(173 citation statements)
references
References 47 publications
1
169
0
3
Order By: Relevance
“…Our data verify that EGCG is more effective in lung cancer cells that overexpress G3BP1 and not as effective in cells with low abundance of the G3BP1 protein. These results indicate that EGCG specifically targets G3BP1 to exert its chemopreventive effects, confirming other reports that EGCG suppresses anchorage-independent lung cancer cell growth (28). Our results provide strong evidence showing that G3BP1 is a direct mediator of EGCG suppression of anchorage-independent lung cancer cell growth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data verify that EGCG is more effective in lung cancer cells that overexpress G3BP1 and not as effective in cells with low abundance of the G3BP1 protein. These results indicate that EGCG specifically targets G3BP1 to exert its chemopreventive effects, confirming other reports that EGCG suppresses anchorage-independent lung cancer cell growth (28). Our results provide strong evidence showing that G3BP1 is a direct mediator of EGCG suppression of anchorage-independent lung cancer cell growth.…”
Section: Discussionsupporting
confidence: 91%
“…Tea has been alleged to provide various beneficial health effects and medicinal efficacy in the prevention and treatment of many diseases (27). EGCG, the primary active ingredient in green tea, has been suggested to provide cancer-preventive activity by regulating multiple signaling transduction pathways as shown in cancer cell lines and animal models of cancer (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…These phase 2 conjugation reactions are particularly important for polyphenols such as epi-gallocatechin-3-gallate (EGCG), which is the most abundant catechin in green tea. EGCG has numerous hydroxyl groups and undergoes extensive phase 2 metabolism, including glucuronidation, sulphation and methylation [37,88]. Several recent studies using liquid chromatography-tandem mass spectrometry (LC-MS/MS) have demonstrated that after ingestion of flavonoids, phase 2 conjugates of the aglycon such as glucuronides, sulphates and methylated metabolites predominate in the blood circulation, rather than the original plant glycoside or aglycon [32,93].…”
Section: Absorption Metabolism and Distribution Of Polyphenolsmentioning
confidence: 99%
“…More detailed, in vivo mouse studies have established that EGCG can function as a strong chemopreventative agent against cancer development and progression (47,48), and epidemiological and preclinical studies have demonstrated that catechins derived from green tea have profound chemopreventative and antitumor effects (38,48,49). The mechanisms by which EGCG is able to produce these effects is wide-ranging and includes e.g.…”
Section: Discussionmentioning
confidence: 99%